A Simplified Method for Determination of Free Fatty Acids for Soluble and Immobilized Lipase Assay - Djagal W. Marseno; Retno Indrati; Yoshiyuki Ohta (Indonesian Association of Food Technologists, 1998)
A simple and rapid method for determination of free fatty acids for soluble and immobilized lipase assay was developed. The free fatty acids could be determined within 10 min with less organic solvent used and the color developed was stable until 60 min. High correlation (r > 0.97) between fatty acids content (2 -10 pmole) and absorbance was observed for fatty acids with carbon number of 6 or higher. Hydrolysis activity of soluble and immobilized lipase could be measured with high sensitivity and reproducibility against incubation time and protein loading. The effect of various substrate concentrations and water against hydrolysis activity could also be measured. The method was suitable for routine analysis such as purification of lipase and continuous hydrolysis of fat and oil.